The Potential of Sharia Advocates In Increasing Community Legal Awareness - Sudarmaji, Waluyo; Ridwan; Maulana, Bani Syarif; Wan Zahari, Wan Ainaa Mardhiah (Advances in Humanities and Contemporary Studies, 2024)
The increase of public awareness about law is an important issue in building the progress of the nation. The emergence of law advocates signifies the contribution on legal aids and community services among the advocates, one of which is in the form of increasing legal awareness. This study aims to analyze the potential of sharia advocates in increasing legal awareness for the community. This study is qualitative research with a sociological juridical approach. The results of the study concluded that the emergence of the advocate law guarantees advocates an active role both in litigation and non-litigation. In terms of litigation, advocates do not merely provide legal assistance to paid clients, but advocates are required to provide free legal assistance to poor people who need legal services (pro bono). Meanwhile, in non-litigation terms, advocates have the responsibility to assist disputing parties to resolve their cases outside the court. Sharia advocates, in addition to providing legal assistance through litigation and non-litigation, also have the potential to carry out Islamic da’wah by conducting education and counseling on sharia laws, both formally and non-formally as a form of effort to increase legal awareness in the Muslim community regarding legal culture.